IMPROVING STUDENTS SPEAKING ABILITY IN CLASS THROUGH THE ROLE PLAY TECHNIQUE - ., Erasma; Sutapa, Y Gatot; Salam, Urai (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2013)
ABSTRAK Penelitian ini dilaksanakan sebagai upaya meningkatkan kemampuan berbicara siswa di kelas VIIA semester dua SMP Negeri 3 Meliau pada Tahun Pelajaran 2012-2013. Metode penelitian ini adalah penelitian tindakan kelas terhadap siswa kelas VII A SMP Negeri 3 Meliau berjumlah 38 Orang. Data diperoleh dari hasil penilaian keterampilan siswa dalam berbicara. Hasil penelitian menunjukan bahwa kemampuan siswa dalam berbicara di kelas dengan menggunakan teknik bermain peran dapat meningkat. Data hasil test menunjukan bahwa rata-rata perolehan nilai siswa pada siklus 1 57,24 dan rata-rata perolehan nilai pada siklus 2 menjadi 66,18 yang berarti kategorinya cukup baik, dan itu berarti bahwa penggunaan teknik bermain peran dalam meningkatkan kemampuan berbicara siswa dikelas dapat digunakan. Kata kunci: Teknik bermain peran, Penelitian tindakan kelas, Kemampuan berbicara. ABSTRACT This research is designed as a research on improving students speaking ability in class to the second semester of the seventh grade class A students of SMP Negeri 3 Meliau in academic year 2012-2013. In this research the researcher used Role play as technique in teaching speaking. The method of this research is called A Classroom Action Research. The subject of this research was seventh grade class A students of SMP Negeri 3 Meliau in academic year 2012-2013 consist of 38 students. The data of this research were collected by using measurement technique that was a performance test to measure students achievements. The findings of this classroom action research showed that speaking ability in class increases by using Role play technique. Based on data analysis the mean score of the students on the first cycle is 57.24 that qualified poor to average, and the mean score of the students on the second cycle is 66.18 that is qualified average to good. It means that action hypothesis the using Role play technique to improve students speaking ability in class is proved. Keywords: Teaching Technique, CAR, Speaking Ability.